Volume 8: Ocean Renewable Energy 2013
DOI: 10.1115/omae2013-11271
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simulation and Tank Test Results of a Semi-Submersible Floating Wind Turbine Under Wind and Wave Loads

Abstract: A model of the Dutch Tri-floater semi-submersible platform equipped with the NREL 5MW wind turbine has been tested in the hydrodynamic and ocean engineering tank of École Centrale Nantes under wind and wave loads. This paper aims at comparing the results obtained with numerical simulations with these experimental results. The numerical model is based on the FAST design code from NREL and a user defined platform load model for calculating hydrodynamic and mooring loads. This hydrodynamic model includes non line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…Comparison between simulation results and model test results for two sea states without wind was presented. Similar comparison of a semi-submersible floater is reported in [19].…”
Section: Hydrodynamic Loadssupporting
confidence: 81%
“…Comparison between simulation results and model test results for two sea states without wind was presented. Similar comparison of a semi-submersible floater is reported in [19].…”
Section: Hydrodynamic Loadssupporting
confidence: 81%
“…Such adverse effects, observable if the plates have a limited submergence compared to their size, have been observed experimentally by Cermelli and Roddier (2005) on a low-draft offshore platform model. Another experimental study by Philippe et al (2013b) has shown pitch motion amplification on a FWT, which was orientatively attributed to heave plate excursion.…”
Section: Semi-submersible Platformmentioning
confidence: 96%
“…Numerous studies involving both the development of computational models and experimental work have been undertaken to date on floating horizontal‐axis wind turbines. Yet these were mainly aimed at investigating the dynamic response of the floating structure . Experimental studies on scaled floating turbines were commonly limited to wave tank tests with the wind generated using upstream air fans .…”
Section: Introductionmentioning
confidence: 99%
“…Yet these were mainly aimed at investigating the dynamic response of the floating structure . Experimental studies on scaled floating turbines were commonly limited to wave tank tests with the wind generated using upstream air fans . The flow quality is thus inferior to that normally found in wind tunnels dedicated for aerodynamic studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation